A comparative study of the electrical properties of undoped schottky junction In/a-Si:H/AZO-Coated-Glass and In/SiNWs/AZO-Coated-Glass Solar Cells - Stephen, Dr Abayomi Adebola (Open Science Journal, 2023)
Plasma enhanced chemical vapour deposition (PECVD) is used to synthesise undoped hydrogenated amorphous thin film silicon (a-Si:H) and silicon nanowire (SiNWs) array for solar cell applications. Indium metal is used as the top contact electrode in Schottky junction configured solar cells devices represented as In/a-Si:H/AZO-coated glass and In/SiNWs/AZO-coated glass respectively. For six solar cell devices on each sample, its observed that charge carrier trap states are observed under dark conditions, despite indium metal's farther position on the various impurities in silicon mid-band gap and minimum temperature for Vapour-Liquid-Solid (VLS) Silicon nanowire growth, which is expected to not produce charge carrier trap states. In/SiNWs/AZO-coated glass solar device demonstrated non-rectifying and ohmic behaviour with no significant measurable solar cell device parameters, while In/a-Si:H/AZO-coated glass showed rectifying and Schottky behaviour with a reported average values of short circuit current (ISC) of (9.522 ± 0.82)A, open circuit voltage (VOC) of (0.305 ± 0.05)V, and ideality factor (n) of (4.7 ± 0.32).